Experimental study on the load bearing behavior of geosynthetic reinforced soil bridge abutments with different facing conditions. Issue 4 (August 2022) - Zhang, Jun; Jia, Yafei; Guo, Wenhao; Zhao, Jianbin; Ling, Jianming; Zheng, Yewei
Abstract: This paper presents an experimental study on reduced-scale model tests of geosynthetic reinforced soil (GRS) bridge abutments with modular block facing, full-height panel facing, and geosynthetic wrapped facing to investigate the influence of facing conditions on the load bearing behavior. The GRS abutment models were constructed using sand backfill and geogrid reinforcement. Test results indicate that footing settlements and facing displacements under the same applied vertical stress generally increase from full-height panel facing abutment, to modular block facing abutment, to geosynthetic wrapped facing abutment. Measured incremental vertical and lateral soil stresses for the two GRS abutments with flexible facing are generally similar, while the GRS abutment with rigid facing has larger stresses. For the GRS abutments with flexible facing, maximum reinforcement tensile strain in each layer typically occurs under the footing for the upper reinforcement layers and near the facing connections for the lower layers. For the full-height panel facing abutment, maximum reinforcement tensile strains generally occur near the facing connections. Highlights: The influence of facing condition on the load bearing behavior of GRS abutments is investigated. The deformation behavior of GRS abutments with different types of facing are compared and discussed. The incremental lateral and vertical soil stresses are compared with the FHWA and AASHTO methods. The reinforcement strain distributions and the corresponding location of maximum strains are presented and discussed.